(untitled) (Palíndromo, 2022)
The portrait of Bethencourt da Silva is a complex composition by the Santa Catarina artist Sebastião Vieira Fernandes. The central character of this work, Bethencourt da Silva, is the creator and maintainer of the Lyceum of Arts and Crafts, where Sebastião Fernandes was educated and worked as a teacher until his last days. The composition created to honor Bethencourt also celebrates the anniversary of the foundation of the Liceu, which, along with the Imperial Academy of Fine Arts, was one of the main centers for art education in Brazil. Through the detailed reading of the figurative elements and the compositional structure, we try to understand a little more of the character of the person portrayed as presented by the painter, and, consequently, recognize from the artist a little of his poetic language. In the same way, it is perceptible that the connection between the artist and the person portrayed, developed by their bond with the Liceu, is materialized in the colors and shapes in this painting.